Metasurface Based on Inverse Design for Maximizing Solar Spectral Absorption. Issue 19 (19th June 2021) - Jiang, Xinpeng; Yuan, Huan; Chen, Dingbo; Zhang, Zhaojian; Du, Te; Ma, Hansi; Yang, Junbo
Abstract: Broadband absorption of sunlight plays a crucial role in applying solar energy. However, despite being a decade‐old technology, there are only a handful of simple metasurfaces designed by conventional methods. This work theoretically combines inverse design with broadband absorption of sunlight to optimize a metasurface that exhibits triple coupling mode resonance for maximizing solar spectral absorption. The metasurface consists of dual‐layer titanium nitride (TiN) cylinder grating arrays, TiN dielectric layers, and silicon nitride layers. The simulation results reveal the high absorptivity of 93% in the range of 250–2450 nm, which covers almost the entire solar spectrum. The advantages of genetic algorithm (GA) including less computational cost and high performance of populations are compared with conventional method. Based on mode analysis, the origin of the observed triple coupling mode resonances is revealed. In addition, the GA‐based metasurface has a high solar–thermal efficiency that includes not only the high absorptivity of 93% in solar spectrum, but also the low emissivity of 21% in infrared band without restriction of polarization and incident angle. The design, which highlights the potential impact on maximizing broadband absorption using simple method to optimize complex coupling, opens a novel approach to study solar–thermal energy harvesting and manipulation. Abstract : This work combines inverse design with broadband absorption of sunlight to optimize metasurface for maximizing solar spectral absorption. The metasurface is consisted of dual‐layer titanium nitride (TiN) cylinder arrays, a TiN dielectric layer, and silicon nitride layers. The simulation results reveal the high absorptivity of 93% in the range of 250–2450 nm, which covers almost the entire solar spectrum.